Analisis Pengaruh Design Pattern Terhadap Pemeliharaan Perangkat Lunak Learning Management System - Kevin, Albertus; Kurniawan, Hans Christian (Yayasan Petra Harapan Bangsa, 2023)
Software development focuses more on functionality so code quality is neglected. Design patterns can support faster development while supporting good code quality thus affecting long-term software maintenance. This research focuses on analyzing the effect of design patterns on software maintenance with open-source learning management system software in terms of design pattern characteristics. Five design patterns were applied and analyzed to assess the implementation method and design pattern characteristics. Testing is done using PHP Metrics. There are nine metrics to measure the complexity, size, cohesion, and dependability of each class. Overall, the design pattern had a good impact. Method templates and mediators have a good impact on cohesion, size, dependability, and complexity. Singletons increased the number of classes. Builders and strategies don't have much impact on size and complexity. Each design pattern generates a new class, so the complexity, dependencies, and size of the code are abstracted into that class.